Strategi Humas dalam Meningkatkan Engagement Pendengar melalui Platform Media Sosial: Studi Penelitian pada Instagram RRI Palembang - Azzahiru, Nursyamsa; Farid, M. Miftah (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
Abstract This study aims to determine and understand the duties and roles of public relations in bridging the gap between the public and institutions so that two-way interaction and communication can occur. Forming concepts and ideas in creating content. Identifying public behavior and needs to make further decisions, as well as providing good service and maintaining the image of the institution. The object of this study is Instagram RRI Palembang (@rri.palembang). The method used is descriptive qualitative, with instruments in the form of interviews and images to obtain more detailed information. After going through interviews and observations, it was found that the total views on @rri.palembang reached 218,5 thousand, interactions 3,2 thousand, followers increased by 255 people, content shared as many as 183, and the optimal schedule for posting on Instagram starts from 6.00-9.00 PM. This study provides a strategy for building engagement with the public, especially for the younger generation.